Analyzing Dengue Transmission Through a Two-Age-Class Host Population Model - Eminugroho Sari; Dwi Lestari; Nikenasih Binatari; Retno Subekti; Fitriana Saptaningtyas (Jambura Journal of Biomathematics (JJBM), 2026)
Age is an important risk factor for vector-borne diseases such as dengue. Children are more exposed to mosquito bites than adults due to behavioral and environmental factors. This study extends the classical host-vector modeling framework by incorporating the human population divided into two age classes, i.e, children and adults. The model also introduces additional key biological parameters, such as $b$, the number of mosquito bites per day; $σ$, the intrinsic growth rate of the mosquito population; and $η$, the relative probability that a mosquito bites an adult rather than a child. We derive the basic reproduction number using the next-generation matrix method and analyze the local stability of the disease-free equilibrium. Furthermore, we obtain sufficient conditions for the local asymptotic stability of the endemic equilibrium in a specific case. Sensitivity analysis is discussed to identify parameters that have the most influence. The numerical simulations are provided to support the theoretical results.